High-volume mucinous ascites secondary to low-grade mucinous neoplasm arising in a mature cystic teratoma: a case report - Speer, Jacquelyn E. F.; Lucy, Adam; Turner, Eric M.; Bath, Natalie; Dal Zotto, Valeria L.; Toboni, Michael D.; Kopecky, Kimberly E. (AME Case Reports; Vol 10 (July 30, 2026): AME Case Reports, 2026)
Background: Low-grade mucinous neoplasms arising within mature ovarian cystic teratomas are rare and represent an uncommon ovarian source of pseudomyxoma peritonei (PMP). Because mucinous ascites and peritoneal disease are most often associated with appendiceal or other gastrointestinal primaries, ovarian-origin mucinous neoplasms may be underrecognized, contributing to diagnostic uncertainty and potential misclassification.Case Description: We report the case of a 30-year-old nulliparous woman who presented with progressively worsening abdominal pain, distension, and respiratory discomfort. Imaging revealed a large, complex abdominopelvic mass with extensive intraperitoneal fluid accumulation. Tumor markers were notable for markedly elevated carcinoembryonic antigen (CEA) with normal cancer antigen 125 (CA125). Aspiration yielded mucinous fluid, and endoscopic gastrointestinal evaluation was unremarkable. Surgical exploration demonstrated a markedly enlarged ovarian mass and a high volume of mucinous intraperitoneal fluid, with no gross appendiceal abnormalities. Approximately 22 L of mucinous material were evacuated. Surgical management included oophorectomy, appendectomy, omentectomy, and peritoneal biopsies. Pathologic evaluation revealed a low-grade mucinous neoplasm arising within a mature cystic teratoma, with immunohistochemical features consistent with gastrointestinal-type differentiation. The postoperative course was uncomplicated, and the patient is undergoing close surveillance with planned interval imaging.Conclusions: This case highlights a rare but clinically significant ovarian source of mucinous peritoneal disease that closely mimics appendiceal pathology. Increased clinical and pathologic awareness of mucinous neoplasms arising within mature cystic teratomas may be important to support accurate diagnosis, appropriate multidisciplinary evaluation, and informed management.